Development and Study of Hybrid Solar and Wind Energy Systems - Mammadov, Fuad (Review of Energy Technologies and Policy Research, 2014)
In the paper is about the realization of autonomous and periodic electricity supply due to the hybrid solar and wind energy system. For this purpose the hybrid system settled in Baku city and Gusar region were firstly studied in the Republic. Initially average annual solar and wind energy potentials of Baku city and Gusar region have been measured. Seperately and together average monthly and annual energy production of hybrid solar and wind energy plant were determined.